1962
DOI: 10.2134/agronj1962.00021962005400050014x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rye Winter Cover Crop on Soil Structure1

Abstract: Synopsis The roots of a rye cover crop were primarily responsible for an improved physical condition of a Nixon sandy loam. Organic matter additions consisting only of the rye top growth had no measurable effect. Three years of cover cropping were necessary before any soil physical differences could be measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 3 publications
0
9
0
1
Order By: Relevance
“…Tisdall and Oades (1982) reference the importance of actively growing roots and fungal hyphae on the stability of soil aggregates, adding strength to the argument for growing winter cover crops during a typically fallow period in a corn and soybean production system in order to help protect and improve the soil. The fibrous root system of cereal rye was likely one cause of the increased MWD (Benoit et al 1962;Villamil et al 2006), as well as fungal hyphae and the decaying organic matter from the dead roots (Tisdall and Oades 1982). Larger, more stable soil aggregates are better able to withstand erosive forces, allow for better water infiltration, and help to prevent surface compaction and runoff (Blanco-Canqui et al 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tisdall and Oades (1982) reference the importance of actively growing roots and fungal hyphae on the stability of soil aggregates, adding strength to the argument for growing winter cover crops during a typically fallow period in a corn and soybean production system in order to help protect and improve the soil. The fibrous root system of cereal rye was likely one cause of the increased MWD (Benoit et al 1962;Villamil et al 2006), as well as fungal hyphae and the decaying organic matter from the dead roots (Tisdall and Oades 1982). Larger, more stable soil aggregates are better able to withstand erosive forces, allow for better water infiltration, and help to prevent surface compaction and runoff (Blanco-Canqui et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…These characteristics were likely to result in substantial biomass production across the broad range of field sites included in the larger study throughout the Midwest. Cereal rye as a cover crop has been shown to have many benefits including weed suppression (Barnes and Putnam 1983), improved soil aggregation and structure (Benoit et al 1962;Villamil et al 2006), decreased bulk density and compaction (Moore et al 2014;Blanco-Canqui et al 2011), and improved soil water retention characteristics (Villamil et al 2006;Basche et al 2016). Other studies have shown no change in soil physical properties other than water stable aggregation, when measured during the cash crop growing season (Steele et al 2012).…”
mentioning
confidence: 99%
“…Mesopores are thought to contain the water between 10 kPa and 1500 kPa, and can be influenced by management such as cover crops in no-till systems (Kay, 1998). The contribution of cover crop roots was found to be essential for improvements to soil aggregate stability to occur, compared to incorporation of only the aboveground plant residue (Benoit et al, 1962). In a maize-soybean rotation in Illinois, found that winter cover crops increased water aggregate stability, soil organic matter and mesoporosity, which in turn increased plant available water.…”
Section: Research Question 3: Which Soil Water Retention Properties Amentioning
confidence: 96%
“…Page and Willard (1947) found significant positive correlations between WSA and maize yield in several clayey soils in Ohio. Benoit, et al (1962) found significant correlations between maize yield and the WSA of a sandy-loam soil only in one out of four years, and attributed this result to adverse weather conditions in that year. De Boodt, et al (1961) concluded that significant correlations of soil structure with crop yield are weather-dependent.…”
Section: Introductionmentioning
confidence: 97%